Shear Characteristics of Cement-Stabilized Sand Reinforced with Waste Polyester Fiber Fabric Blocks - Xiangfeng Lv; Hongyuan Zhou (Advances in Materials Science and Engineering)
The present paper is devoted to investigate the effects of waste polyester fiber fabric blocks on the strength and mechanical behavior of cemented sand. In the investigation, samples were prepared at four different percentages of waste polyester fiber fabric block content (0.0%, 0.5%, 1.0%, and 1.5% by weight of soil) and two different aspect ratios (2 : 1 and 3 : 1), and conventional triaxial compression tests were carried out after the curing period. The test results indicated that the addition of fibers increased peak and residual shear strengths of cemented sand and changed its brittle behavior to a more ductile one. As the fabric block content increased, the brittleness index and initial stiffness decreased, and the peak strain and internal friction angle increased. The optimal combination of the content and aspect ratio was determined to be 0.5% and 3 : 1. The integration of the fabric blocks with the cemented sand matrix was analyzed by using the scanning electron microscopy (SEM). It is found that the reinforcement effect is related to the bond strength and friction at the interface. The micromechanical properties of the fiber/matrix interface were influenced by the undulations between the fabric block components. In summary, this study presented a low-cost and environment-friendly method for reinforcing cement-stabilized sand.